2014
DOI: 10.3989/gya.110913
|View full text |Cite
|
Sign up to set email alerts
|

La Antracnosis del olivo y su efecto en la calidad del aceite

Abstract: SUMMARY:Olive Anthracnose and its effect on oil quality. Olive (Olea europaea subsp. europaea var. europaea) is one of the first domesticated and cultivated trees that is widely distributed in the Mediterranean regions. The Anthracnose, caused by the two complex fungal species Colletotrichum acutatum and C. gloeosporioides, is the most important disease adversely affecting the olive oil quality. Even so, the effect of Anthracnose on oil quality is largely unknown and many questions remain unanswered. This offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
84
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 35 publications
(74 reference statements)
2
84
0
2
Order By: Relevance
“…It is well documented that olive oil from affected fruit shows undesirable physicochemical and organoleptic parameters, leading to significant economic losses (Moral et al . ; Romero et al . ).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is well documented that olive oil from affected fruit shows undesirable physicochemical and organoleptic parameters, leading to significant economic losses (Moral et al . ; Romero et al . ).…”
Section: Introductionmentioning
confidence: 95%
“…; Moral et al . ). The management of the disease includes critical factors such as: (i) fungicide applications should completely cover the olive canopy for optimum control (Trapero et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…To date, the relevance of C. acutatum infection in olive trees has prompted the evaluation of its deleterious effect on the chemical characteristics and sensory properties of olive fruits and thus, on the quality of the olive oils obtained . In this concern, previous works have shown that, regarding olive oil, the main chemical characteristics affected by C. acutatum are the increase of free acidity and the decrease of the phenolic content and antioxidant activity (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…5 To date, the relevance of C. acutatum infection in olive trees has prompted the evaluation of its deleterious effect on the chemical characteristics and sensory properties of olive fruits and thus, on the quality of the olive oils obtained. [6][7][8][9] In this concern, previous works have shown that, regarding olive oil, the main chemical characteristics affected by C. acutatum are the increase of free acidity and the decrease of the phenolic content and antioxidant activity (unpublished data). However, to the best of our knowledge, the effect of this pathogen on the phenolic profile of olive fruits, which is strongly dependent on a myriad of factors including the cultivar considered, maturation stage, and stressing growing conditions (including fungus infection), [10][11][12][13] has not been thoroughly assessed so far.…”
mentioning
confidence: 99%